2015
DOI: 10.1136/vr.102755
|View full text |Cite
|
Sign up to set email alerts
|

Influence of porcine circovirus type 2 vaccination on the probability and severity of pneumonia detected postmortem

Abstract: To evaluate the influence of porcine circovirus type 2 vaccination (PCV-2) on the probability and severity of pneumonia, postmortem findings of 247,505 pigs slaughtered between 2008 and 2011 were analysed by applying a cumulative link mixed model. Three major effects could be observed: (1) PCV-2 vaccination significantly (P<0.01) reduced the odds (coefficient: −0.05) of postmortem findings of mild, moderate and severe pneumonia for vaccinated pigs. (2) Pigs from fattening farms were less likely (coefficient: −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…While on farrow-to-finish farms vaccinating against PCV-2, a reduction in antimicrobial consumption of approximately 15 per cent was determined, statistical modelling revealed a much larger estimated reduction in antibiotic use of 67 per cent on finishing farms using PCV-2 vaccination over the study period. A similar farm type-related effect of PCV-2 vaccination was also found in a previous retrospective study on the prevalence of pneumonia postmortem findings in slaughter pigs (Raith and others 2015). Two main effects are presumably responsible for this relationship between farm type and the effect of the PCV-2 vaccination programme.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…While on farrow-to-finish farms vaccinating against PCV-2, a reduction in antimicrobial consumption of approximately 15 per cent was determined, statistical modelling revealed a much larger estimated reduction in antibiotic use of 67 per cent on finishing farms using PCV-2 vaccination over the study period. A similar farm type-related effect of PCV-2 vaccination was also found in a previous retrospective study on the prevalence of pneumonia postmortem findings in slaughter pigs (Raith and others 2015). Two main effects are presumably responsible for this relationship between farm type and the effect of the PCV-2 vaccination programme.…”
Section: Discussionsupporting
confidence: 84%
“…The benefits of PCV-2 vaccination in relation to respiratory diseases have already been shown by a number of studies (Fachinger and others 2008, Kixmöller and others 2008, Raith and others 2015) and it has been suggested that this positive effect is primarily due to a reduction in secondary bacterial infections (Fachinger and others 2008, Kixmöller and others 2008). Alban and others (2013) have previously reported a similar observation in Denmark, where the increased use of vaccines against respiratory diseases (including PCV-2-related infections) corresponded to a decline in the use of antimicrobials for the treatment of respiratory infections in all age groups.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Western France (Brittany), Porcine Respiratory Disease Complex (PRDC) has been extensively studied; its main infectious risk factors are Mycoplasma hyopneumoniae , Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) and the Swine influenza virus (SIV) H1N1, while PCV2 is less frequently identified [ 7 ]. However, an Austrian study of over 254,000 slaughtered pigs demonstrated that finishers raised on farrow-to-finish farms and that had not been vaccinated against PCV2 were at significantly higher risk of presenting pneumonia post-mortem than vaccinated fatteners from finisher farms [ 8 ]. Interestingly, Austria and Brittany have similar pig farm size and production systems.…”
Section: Introductionmentioning
confidence: 99%